Impact of automated response systems on in‐class cell phone use. Issue 5 (30th May 2019) - Moorleghen, Dylan M.; Oli, Naresh; Crowe, Alison J.; Liepkalns, Justine S.; Self, Casey J.; Doherty, Jennifer H.
Abstract: Cell phones have long been known as a potential distraction from attention intensive activities such as studying and driving. Many, however, are developing the cell phone as a powerful tool to augment some of these same activities. Audience response systems (ARSs) are a type of teaching tool that allows educators to poll audience members in real time. Increasingly, cell phones are being integrated into ARSs to make them more versatile and affordable. As cell phones and other personal electronic devices (tablets, laptops) are becoming more common classroom learning tools, we sought to explore how student cell phone use is impacted by this change. Additionally, we studied how a student's seat location and how the time during a term impacts students' cell phone use. To measure student cell phone use in lecture, we observed introductory biology classes at the University of Washington and recorded when students' cell phones were visible. We found that students sitting in the back of the room showed an increased likelihood of having a cell phone out. However contrary to our expectations, students using personal device (cell phone) based polling technology were no more likely to be using cell phones during lecture than their peers using traditional ARSs. Our results suggest that the downsides to using cell phones as teaching tools may be limited. © 2019 The International Union of Biochemistry and Molecular Biology, 47(5):538–546, 2019.